Comparison between European Protestant and Catholic Economic Development through Modern Painting - Bernadett Balassa (DETUROPE)
Since Max Weber, economists suggest that religious activity affects the European economic development, and this hypothesis was proven between the seventeenth and nineteenth centuries. Accordingly Protestant economic thinking accelerated the evolving system of capitalism, giving adequate attitudes to the accumulation of wealth. This research supposes that the mentioned capitalist approaches have their own impressions on visual arts, particularly on modern painting. It examines almost nine hundred religious paintings from the fifteenth to nineteenth centuries, investigating signs of business activities on the artworks. This form of qualitative examination apply the methodology of content analysis. As a result of the study the former hypothesis of Weber could be verified from multidisciplinary approach.